2015
DOI: 10.1126/science.1258100
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-λ cures persistent murine norovirus infection in the absence of adaptive immunity

Abstract: Norovirus gastroenteritis is a major public health burden worldwide. Although fecal shedding is important for transmission of enteric viruses, little is known about the immune factors that restrict persistent enteric infection. We report here that while the cytokines interferon-α (IFN-α) and IFN-β prevented the systemic spread of murine norovirus (MNoV), only IFN-λ controlled persistent enteric infection. Infection-dependent induction of IFN-λ was governed by the MNoV capsid protein and correlated with diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
340
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(362 citation statements)
references
References 36 publications
18
340
1
3
Order By: Relevance
“…Treatment with type I IFN-β was significantly more effective than type III IFN at restricting HRV replication. This differs from reports in mice, in which exogenous treatment with IFN-λ is more protective against enteric viral replication than type I IFN (55,56), and type I IFN is primarily considered to inhibit systemic spread of enteric viruses (17,56,75). This difference may be a result of the type I IFN subtype tested; previous studies in mice and HIEs used an IFN-α subtype rather than IFN-β for exogenous treatment (17,55,56,83); however, IFN-α2 was significantly weaker than IFN-β in restricting HRV growth in HIEs.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Treatment with type I IFN-β was significantly more effective than type III IFN at restricting HRV replication. This differs from reports in mice, in which exogenous treatment with IFN-λ is more protective against enteric viral replication than type I IFN (55,56), and type I IFN is primarily considered to inhibit systemic spread of enteric viruses (17,56,75). This difference may be a result of the type I IFN subtype tested; previous studies in mice and HIEs used an IFN-α subtype rather than IFN-β for exogenous treatment (17,55,56,83); however, IFN-α2 was significantly weaker than IFN-β in restricting HRV growth in HIEs.…”
Section: Discussioncontrasting
confidence: 54%
“…This result was unexpected because enteric viral replication (rotavirus, reovirus, murine norovirus) is enhanced in mice lacking the type III IFN receptor (54)(55)(56)75), even though it is notable that neutralization of the type III IFN response had a limited effect on reovirus replication (approximately twofold increase in viral transcripts) in a human colonic transformed cell line (70). The basis for the apparent discrepancy may be multifactorial and include differences in how the IFN system was blocked (neutralizing antibodies vs. receptor KOs), development of alternate compensatory pathways in IFN-KO mice, and/or differences in human and mouse type III IFN subtype expression (37,38).…”
Section: Discussionmentioning
confidence: 88%
“…Important areas of future research will be to determine whether the enterocytes transcytosing NoVs recognize pathogen-associated molecular patterns (PAMPs) and contribute to the antiviral immune response; and whether antiviral immune responses that prevent transcytosis are important in controlling NoV infection. Related to the latter idea, a recent report demonstrated that the type III interferon (IFN), or IFN-l, response is critical to control persistent enteric infection by MuNoVs in a manner requiring IFN-l receptor expression on nonhematopoietic cells 40 ; thus, one could speculate that IFN-l-mediated signaling suppresses transcytosis of NoVs and this prevents persistence establishment.…”
Section: A Gii4-sydney Human Norovirus Infects B Cells In Vitromentioning
confidence: 99%
“…The site of persistence is reported to be the intestine, where CR6 is present for many weeks after infection (20). It was recently shown that both wildtype and IFNAR Ϫ/Ϫ -positive mice were cured of an ongoing MNV.CR6 infection following treatment with gamma interferon (IFN-) (21).…”
mentioning
confidence: 99%